Short term effects of anodal cerebellar vs. anodal cerebral transcranial direct current stimulation in stroke patients, a randomized control trial - Qurat-ul-ain,; Ahmad, Zafran; Ishtiaq, Summaiya; Ilyas, Saad; Shahid, Irum; Tariq, Iqbal; Malik, Arshad Nawaz; Liu, Tian; Wang, Jue (Frontiers in Neuroscience, 2022)
Background Balance and gait impairments are major motor deficits in stroke patients that require intensive neuro-rehabilitation. Anodal transcranial direct current stimulation is a neuro-modulatory technique recently used in stroke patients for balance and gait improvement. Majority of studies focusing on tDCS have assessed its effects on cerebral motor cortex and more recently cerebellum as well but to our best knowledge the comparison of stimulating these two regions in stroke patients is not investigated so far. Objective The current study aimed to compare the effect of anodal transcranial direct current stimulation on cerebellar and cerebral motor cortex M1 in stroke patients. Materials and methods This double-blinded, parallel, randomized, sham controlled trial included 66 patients with a first-ever ischemic stroke were recruited into three groups; Cerebellar stimulation group (CbSG), M1 Stimulation Group (MSG), and Sham stimulation group (SSG). A total of three sessions of anodal transcranial direct current stimulation were given on consecutive days in addition to non-immersive virtual reality using Xbox 360 with kinect. Anodal tDCS with an intensity of 2 mA was applied for a duration of 20 min. Primary outcome measures berg balance scale (BBS), timed up and go test (TUG), BESTest Balance Evaluation–Systems Test (BESTest) and secondary outcomes measures montreal cognitive assessment (MoCA), mini mental state examination (MMSE), Johns Hopkins Fall Risk Assessment Tool (JHFRAT), twenty five feet walk test (25FWT), six minute walk test (6MWT), and tDCS Adverse Effects was assessed before initiation of treatment (T0) and at the end of third session of stimulation (T1). Results The results of between group’s analysis using mean difference showed a significant difference with p-value <0.05 for balance (BBS, TUG, BESTest), walking ability (6MWT, 25FWT), risk of fall (JHFRAT). Cognitive function did not show any significant change among the groups for MoCA with p-value >0.05 but MMSE was improved having significant p-value (p = 0.013). However, 6MWT and 25FWT showed non-significant results for both between group and within group analysis. In pairwise comparison both the cerebellar and cerebral stimulation groups showed Significant difference with p-value <0.05 in comparison to sham stimulation; BBS (cerebellar vs. sham p ≤ 0.001, cerebral vs. sham p = 0.011), TUG (cerebellar vs. sham p = 0.001, cerebral vs. sham p = 0.041), Bestest (cerebellar vs. sham p = 0.007, cerebral vs. sham p = 0.003). Whereas for JHFRAT only cerebellar stimulation in comparison to sham and motor cortex stimulation showed significant improvements (cerebellar vs. M1 p = 0.037, cerebellar vs. sham p = 0.037). MMSE showed significant improvement in M1 stimulation (M1 vs. cerebellar p = 0.036, M1 vs. sham p = 0.011). Conclusion Findings of the study suggest anodal tDCS stimulation of the cerebellum and cerebral motor cortex both improves gait, balance and risk of fall in stroke patients. However, both stimulation sites do not induce any notable improvement in cognitive function. Effects of both stimulation sites have similar effects on mobility in stroke patients.